PERANAN ORANG TUA DALAM MENGAJARKAN PENDIDIKAN SHALAT PADA ANAK SEJAK USIA DINI - Enny Nazrah Pulungan (Universitas Islam Negeri Sumatera Utara, 2018)
The child is a trust given by Allah Swt. to the parents, so it is fitting that if the mandate is always well preserved, one of the way is to educate them properly, especially the issue of religious education such as teaching them to perform prayers, so big and important role parents in educating their children from an early age, even since the child is still in the womb, if all goes well it will be a child to be a good person, including children will obey the command of Allah Swt. And will be a good provision for their lives in the future.Kata kunci : peranan, pendidikan, shalat, usia dini.